Encountering the New Testament : a historical and theological survey - Elwell, Walter A.; Yarbrough, Robert W. (Grand Rapids, MI : Baker Academic, 2013)
"Studying the New Testament can be an exciting-and intimidating-experience. This readable survey is designed to make the adventure less daunting and more rewarding. Two experienced classroom teachers offer a new edition of their bestselling and award-winning textbook, now with updated content and a new interior design. Other distinguishing features include: abundant images, maps, and charts-all in full color; sidebars that address ethical and theological concerns and provide primary source material; focus boxes isolating key issues; chapter outlines, learning objectives, and summaries; study questions. An accompanying website will offer a wide array of resources for students and professors. Resources for students include flash cards, self quizzes, and chapter summaries. Resources for professors include suggestions for class activities as well as an instructor's manual and test bank. Students of the New Testament will find this introductory text both informative and engaging" -- Publisher description.
Includes bibliographical references (p. 391-408) and index.
Keywords: Bible. -- Introductions